Stability Analysis for Markovian Jump Neutral Systems with Mixed Delays and Partially Known Transition Rates - Lianglin Xiong; Xiaobing Zhou; Jie Qiu; Jing Lei (Abstract and Applied Analysis)
The delay-dependent stability problem is studied for Markovian jump neutral systems with partial information on transition probabilities, and the considered delays are mixed and model dependent. By constructing the new stochastic Lyapunov-Krasovskii functional, which combined the introduced free matrices with the analysis technique of matrix inequalities, a sufficient condition for the systems with fully known transition rates is firstly established. Then, making full use of the transition rate matrix, the results are obtained for the other case, and the uncertain neutral Markovian jump system with incomplete transition rates is also considered. Finally, to show the validity of the obtained results, three numerical examples are provided.